Penurunan Kadar Glukosa Darah Mencit (Mus Musculus) yang Diinduksi Hiperglikemia oleh Ekstrak Etanol Daun Sirsak (Annona muricata L.) - Claudia Sindi; Betty Fitriyasti; Gangga Mahatma; Salmi Salmi (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2022)
Hyperglycemia is one of the diabetes mellitus characteristics. Soursop leaves (Annona muricata L.) has been used traditionally to reduce blood glucose level and clinically need to be proven. The aim of this study was to observe the effect of ethanol extract of soursop leaves (EDS) on blood glucose levels of hyperglycemia mice (Mus musculus). This was an experimental study with a pre-post test control group design. Thirty mice was used as animal models and was hyperglycemia induced by alloxan 150mg/kg b.w, respectively. Treatment EDS has been given for 14 days with the variation of doses; 200 mg/Kg b.w, 300 mg/Kg b.w, and 400 mg/Kg bw. Fasting blood glucose level was measured before and after EDS treatment by glucocheck. Data were analyzed by ANOVA and Duncan for further tests to evaluate the effect of EDS while the difference in blood glucose levels in pre-post treament was analyzed by paired t-test. The result showed that EDS significantly reduced blood glucose levels (p < 0.05). EDS with 400 mg/Kg bw dose showed the strongest effect in reducing glucose levels, followed by 300 mg/Kg b.w and 200 mg/Kg b.w doses. In conclusion, EDS has the potential to develop as an agent to reduce blood glucose in diabetes mellitus.